A multidimensional generalization of the Rutishauser qd-algorithm - Dmytryshyn, R.I. (Carpathian Mathematical Publications, 2016)
In this paper the regular multidimensional C-fraction with independent variables, which is a generalization of regular C-fraction, is considered. An algorithm of calculation of the coefficients of the regular multidimensional C-fraction with independent variables correspondence to a given formal multiple power series is constructed. Necessary and sufficient conditions of the existence of this algorithm are established. The above mentioned algorithm is a multidimensional generalization of the Rutishauser qd-algorithm.